2012
DOI: 10.1038/ki.2012.256
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protein, microRNA, and mRNA yields using different methods of urinary exosome isolation for the discovery of kidney disease biomarkers

Abstract: Urinary exosomes are 40-100 nm vesicles containing protein, mRNA, and microRNA that may serve as biomarkers of renal dysfunction and structural injury. Currently, there is a need for more sensitive and specific biomarkers of renal injury and disease progression. Here we sought to identify the best exosome isolation methods for both proteomic analysis and RNA profiling as a first step for biomarker discovery. We used six different protocols; three were based on ultracentrifugation, one used a nanomembrane conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
445
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(454 citation statements)
references
References 30 publications
6
445
0
3
Order By: Relevance
“…Previous studies suggested that urinary miRNAs, like circulating miRNAs in other body fluids, are derived from tissues and cells in the presence of ongoing disease (32,33). In general, cellular miRNAs can passively leak from damaged cells or can be actively secreted into the extracellular space or circulation via the microvesicle pathway (34,35) or within HDL protein complexes (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that urinary miRNAs, like circulating miRNAs in other body fluids, are derived from tissues and cells in the presence of ongoing disease (32,33). In general, cellular miRNAs can passively leak from damaged cells or can be actively secreted into the extracellular space or circulation via the microvesicle pathway (34,35) or within HDL protein complexes (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are small vesicles of about 40-100 nm that are secreted from cells into extracellular fluid, and are found in different bodily fluids, such blood, blood derivatives, urine, and amniotic fluid. Exosomes are produced by all cell types and have a molecular phenotype, which largely reflects that of a parent cell (43,44) The contents of exosomes reflect the origin and the physiological status of the source cells, and thus exosomal RNAs, such as DENND1A.V2, can serve as biomarkers for various diseases. These data further confirm our findings in that DENND1A.V2 mRNA is increased in PCOS, and provide the basis for a potential noninvasive diagnostic for PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, exosomes have been found as a robust source of urinary biomarkers, showing the presence after digital rectal examination of high levels of PCA3 and TMPRSS2-ERG in urinary exosomes [12]. However, no studies are currently available about miRNAs in urinary exosomes in PCa, even when they have been widely explored in benign nephropathies [119,120]. Table 4 presents published results about miRNAs in urine, showing AUCs between 0.639 and 0.769 [49,86,88,98,[121][122][123][124][125][126][127][128].…”
Section: Mirnas In Urine In Prostate Cancermentioning
confidence: 99%